Local chemistry–electrochemistry and stress corrosion susceptibility of X80 steel below disbonded coating in acidic soil environment under cathodic protection. (20th May 2020) - Ma, Hongchi; Zhao, Bo; Liu, Zhiyong; Du, Cuiwei; Shou, Binan
Highlights: The local chemistry-electrochemistry underneath disbonded coating were investigated. A considerably low pH and remarkable concentration of Cl− were observed at the bottom of disbonded coating. The simulated solutions in the crevice were established and SCC susceptibility was evaluated. Abstract: In this study, local chemical and electrochemical states underneath disbonded coatings were investigated using a simulated system. Moreover, the stress corrosion cracking (SCC) susceptibility of X80 steel at different positions was evaluated. Results demonstrated that the microenvironment underneath the disbonded coating changed considerably under cathodic protection (CP). The dissolved oxygen content dropped quickly and transformed into anaerobic state immediately. The pH at the bottom of disbonded coating evolved into an acidity of ~5, accompanied by a remarkable concentration of Cl −, which were probably responsible for the severe corrosion and high SCC susceptibility at the crevice bottom. By contrast, the middle part of the disbonded coating had low SCC susceptibility because of effective CP and weak hydrogen evolution.